A Prospective Analysis of Dynamic Loss of Breast Projection in Tissue Expander-Implant Reconstruction - Mioton, Lauren M; Jordan, Sumanas W; Kim, John YS (Archives of Plastic Surgery, 2015)
Background Breast projection is a critical element of breast reconstruction aesthetics, but little has been published regarding breast projection as the firm expander is changed to a softer implant. Quantitative data representing this loss in projection may enhance patient education and improve our management of patient expectations.Methods Female patients who were undergoing immediate tissue-expander breast reconstruction with the senior author were enrolled in this prospective study. Three-dimensional camera software was used for all patient photographs and data analysis. Projection was calculated as the distance between the chest wall and the point of maximal projection of the breast form. Values were calculated for final tissue expander expansion and at varying intervals 3, 6, and 12 months after implant placement.Results Fourteen breasts from 12 patients were included in the final analysis. Twelve of the 14 breasts had a loss of projection at three months following the implant placement or beyond. The percentage of projection lost in these 12 breasts ranged from 6.30% to 43.4%, with an average loss of projection of 21.05%.Conclusions This study is the first prospective quantitative analysis of temporal changes in breast projection after expander-implant reconstruction. By prospectively capturing projection data with three-dimensional photographic software, we reveal a loss of projection in this population by three months post-implant exchange. These findings will not only aid in managing patient expectations, but our methodology provides a foundation for future objective studies of the breast form.
Keywords: Breast; Breast implants; Esthetics